2011
DOI: 10.1007/s10841-011-9427-2
|View full text |Cite
|
Sign up to set email alerts
|

Can ants be used as indicators of environmental impacts caused by arsenic?

Abstract: We evaluated ants as bioindicators of environmental impacts caused by arsenic residuals in the soil. We tested the hypotheses that the presence of arsenic in the soil affects: (1) estimates of resources and habitat condition for arboreal and epigaeic ants; (2) species richness of arboreal and epigaeic ants and (3) arboreal and epigaeic ant species composition. Ants were sampled at an inactivated raticide factory in Nova Lima, Minas Gerais, Brasil, which used arsenic as one of its main byproducts. The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 47 publications
(46 reference statements)
0
11
0
6
Order By: Relevance
“…Igualmente, son consideradas ingenieras del suelo , por sus diversas funciones que inciden directa e indirectamente en la estructura y funcionamiento de los ecosistemas (Vasconcelos, 1999;Vasconcelos & Laurance, 2005). Adicionalmente, debido a su resilencia ante perturbaciones antropogénicas, han sido utilizadas como grupo bioindicador de alteraciones ambientales (Pais & Varanda, 2010;Ribas et al, 2012;Guzmán-Mendoza, Castaño-Meneses, & Nuñez-Palenius, 2016).…”
unclassified
“…Igualmente, son consideradas ingenieras del suelo , por sus diversas funciones que inciden directa e indirectamente en la estructura y funcionamiento de los ecosistemas (Vasconcelos, 1999;Vasconcelos & Laurance, 2005). Adicionalmente, debido a su resilencia ante perturbaciones antropogénicas, han sido utilizadas como grupo bioindicador de alteraciones ambientales (Pais & Varanda, 2010;Ribas et al, 2012;Guzmán-Mendoza, Castaño-Meneses, & Nuñez-Palenius, 2016).…”
unclassified
“…Ceres, Viçosa, v. 61, Suplemento, p. 800-807, nov/dez, 2014 1999; Ribas et al, 2012). Elas foram estudadas em diversos ambientes, como: áreas de reabilitação de minas, na Austrália (Majer & Nichols, 1998), na África do Sul (Majer & Kock, 1992) e no Brasil (Oliveira & Della Lucia, 1992;Majer, 1996;Santos et al, 2008); em áre-as com metais pesados (Ribas et al, 2012); em áreas de cultivo agrícola (Peck et al, 1998); em avaliação de distúrbio em florestas tropicais (Marinho et al, 2002;Delabie et al, 2006;Leal et al, 2012;Miranda et al,2013) e, ainda, em áreas cultivadas tratadas com inseticidas (Couto et al, 2010;Pereira et al 2010) e herbicidas .…”
Section: Insetos Como Potenciais Bioindicadores De Qualidade Ambientalunclassified
“…Therefore, several studies have shown that ants have potential for use as bioindicators of environmental quality, in natural or altered areas (RIBAS et al, 2012a). Ants have been studied in various types of environments and situations, such as areas subjected to burning (BOSCARDIN et al, 2014); contaminated areas (RIBAS et al, 2012c); agroforestry systems and agroecosystems (GONZÁLEZ-VALDIVIA et al, 2013;RAMÍREZ et al, 2012); crop-livestock systems (CREPALDI et al, 2014); agricultural crops (COUTO et al,. 2010); in the rehabilitation of mined areas and degraded areas (ROSADO et al, 2014, RIBAS et al, 2012b, ROCHA et al, 2015; in revegetation of riparian areas (GOLLAN et al, 2011); and in forest disturbances (LEAL et al,.…”
Section: Introductionmentioning
confidence: 99%